VIKOR-Based Assessment of Indonesia’s Sharia-Compliant Peer-to-Peer Lending Platforms - Itishom Al Khoiry; Ika Menarianti; Noventia Karina Putri (Universitas Stikubank, 2026)
This study applies the VIKOR method to evaluate six Sharia compliant peer to peer (P2P) lending platforms in Indonesia: Ethis, Qazwa, Ammana, Dana Syariah, Alami Sharia, and Duha Syariah. The evaluation focuses on five key criteria: default risk, platform reputation, regulatory compliance and legal protection, return on investment and transparency, and platform sustainability. Criteria weights were determined using the Rank Sum Weighting method, and platform scores were obtained through structured user evaluations. VIKOR, a multi criteria decision making method, ranks alternatives by measuring their closeness to an ideal solution, enabling fair comparison when trade offs exist between conflicting criteria. The method reveals clear distinctions among platforms, enabling balanced, compromise based evaluation aligned with Sharia principles. It offers a practical decision support tool for investors and contributes to the broader application of multi criteria methods in ethical fintech ecosystems across emerging markets.